👤

dane są wyrażenia algebraiczne f i g wyznacz f+g oraz f-g
c)F=a²-4, G=8-a²
d) F-2x-y, G= -(x-2y)
e)F=-(2a-b), G=2a+b
f) F=-(a-b), G+=(a+b)
Potrzebuje teraz


Odpowiedź :

c)

F+G=(a²-4)+(8-a²)=-4+8=4

F-G=(a²-4)-(8-a²)=a²-4-8+a²=2a²-12

d)

Dla F=2x-y

F+G=(2x-y)+(-(x-2y))=2x-y-x+2y

F-G=(2x-y)-(-(x-2y))=2x-y+x-2y=3x-3y

Dla F=-(2x-y)

F+G=-(2x-y)+(-(x-2y))=-2x+y-x+2y

F-G=-(2x-y)-(-(x-2y))=-2x+y+x-2y=-x-y

e)

F+G=-(2a-b)+(2a+b)=-2a+b+2a+b=2b

F-G=-(2a-b)-(2a+b)=-2a+b-2a-b

f)

F+G=-(a-b)+(a+b)=-a+b+a+b=2b

F-G=-(a-b)-(a+b)=-a+b-a-b=-2a